-2(x-6)=-5x+15

Simple and best practice solution for -2(x-6)=-5x+15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(x-6)=-5x+15 equation:



-2(x-6)=-5x+15
We move all terms to the left:
-2(x-6)-(-5x+15)=0
We multiply parentheses
-2x-(-5x+15)+12=0
We get rid of parentheses
-2x+5x-15+12=0
We add all the numbers together, and all the variables
3x-3=0
We move all terms containing x to the left, all other terms to the right
3x=3
x=3/3
x=1

See similar equations:

| x-5/5=9/10 | | 4-7(v-9)=-7-6(v-10) | | 27+5=2x+8 | | 27+5=2x-8 | | 2x-4=3.2 | | 10v-9v+2=8 | | 36k=1,908 | | 8÷2x^2=16 | | 4(3n-5)+5(5n+2)=3n+92 | | 24=2x-13 | | 24=2x-13.5 | | 70-x=249 | | 2x^2*8=26 | | (X+1)x(x+1)-2x=XxX+2 | | 7+s=-8 | | 5(2c+6)=80 | | 23+8x=-(2x-12)+10(x+10) | | 9b-4b-4=11 | | 4/3p=-12 | | 5(2m+2)+6(3m-5)=64 | | 0.5k-4=6. | | b-2+6b=36 | | 6/x=11 | | 9b-4b-4=1 | | b-2-6b=36 | | 1/11y+3=-1 | | 6+s=-9 | | -84+14x=3x+98 | | 4+2(8x-11)=1-7(10x-5) | | 3w+6+w=4w+4+10 | | 8x+3-6x=19 | | (x+9)^2+64=0 |

Equations solver categories